# How do you solve #(x+2)/3+(x-3)/4=1#?

See the entire solution process below:

By multiplying both sides of the equation by the common denominator of the two fractions, we can first eliminate the fractions.

The terms in parenthesis can now be expanded, and on the left side of the equation, we can group and combine like terms:

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation (x+2)/3 + (x-3)/4 = 1, you can follow these steps:

- Multiply every term in the equation by the least common denominator (LCD) of 3 and 4, which is 12. This will eliminate the denominators.

12 * [(x+2)/3] + 12 * [(x-3)/4] = 12 * 1

4(x+2) + 3(x-3) = 12

- Distribute the multiplication on both sides of the equation.

4x + 8 + 3x - 9 = 12

- Combine like terms on both sides.

7x - 1 = 12

- Isolate the variable term by adding 1 to both sides.

7x = 13

- Finally, solve for x by dividing both sides by 7.

x = 13/7

Therefore, the solution to the equation (x+2)/3 + (x-3)/4 = 1 is x = 13/7.

By signing up, you agree to our Terms of Service and Privacy Policy

- How do you simplify rational equations #[a / (a+1)] - [1 / (a-1)]#?
- How do you combine #[(2x + y)/(x - y)] - [(3x - y)/(x + y)] - [(5x + 2y)/(y^2 - x^2)]#?
- How do you solve #10/(3x)-8=2/x# and find any extraneous solutions?
- Does the set of all #n#th roots of unity form a group under multiplication?
- Which equation is the inverse variation relationship for the following quantities y =-12 when x = 5?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7